Estudo da liberação de fragrâncias provenientes de óleos essenciais a partir de partículas poliméricas - Silva, Caroline Garcia Finkler da (2020)
Achyrocline satureioides and Hedychium coronarium are a native and an invasive plant, respectively, from the Brazilian flora. Studies with essential oils of these plants show their great applicability in the perfume industry. However, characteristics such as high volatility, low water solubility and susceptibility to degradation by physical and chemical agents can easily degrade essential oils, compromising their odor quality. Therefore, the present work pursues to protect the volatile compounds present in essential oils through encapsulation in biopolymer. The encapsulation technique adopted (nanoprecipitation) consists of a nano-sized physical coating of the active core. The optimal ratio polymer/oil for the formulations was 1:3, which yielded particle diameters of 178 nm and 159 nm for particles with Achyrocline satureioides and Hedychium coronarium oils, respectively. The morphology was evaluated by scanning electron microscopy (SEM) and transmission microscopy (TEM), the inclusion of oils in the polymer was confirmed by thermogravimetric analysis (TGA). The formulations pH remained stable for 90 days and the controlled release of the compounds was evaluated through antioxidant activity analysis. The diffusion of odorous compounds in air from the formulations was evaluated over time and mathematically modeled Peppas (1985).